Who Needs the Sociology of Health and Illness? A New Agenda for Responsive and Interdisciplinary Sociology of Health and Medicine - Karvonen, Sakari; Kestilä, Laura M.; Mäki-Opas, Tomi E. (Frontiers in Sociology, 2018)
Health and medicine are key areas of sociological specialisation, but in the face of rapid global challenges, they are changing. The need for change is becoming more and more urgent and the relevance of some of the traditional approaches, frameworks and theoretical perspectives should be evaluated. The aim of this article is to reflect on this issue and to explore what could be done in response to scientific and societal developments. We argue that more innovative approaches and better research questions would guide us to be more responsive as medical sociologists. In particular, we think that interdisciplinary and translative work hold untapped potentials for our field.